Evaluation of interstrain differences in fıtness components of Drosophila melanogaster strains with neurological disorders - Глянько, О. В.; Воробйова, Л. І. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
Some components of fitness and locomotor activity of Drosophila melanogaster strains Sh14, slo1, paraST76 with neurological mutations that affect ion channels have been studied in comparison to wild type strains Canton-S and Oregon. The genotype influence on fertility, vitality and locomotor activity of imago has been observed. Sex differences in locomotor activity were established only for a wild type strain C-S. Abnormal work of ion channels effect on mechanisms of neurodegenerations and the formation of fitness of drosophila is discussed.